Three-Dimensional Discrete Element Analysis of Crushing Characteristics of Calcareous Sand Particles. (18th March 2022) - Lu, Zucheng; Hou, Heying; Jiang, Pengming; Wang, Qing; Li, Tianxiang; Pan, Zhuojie
Abstract : Particle crushing is an important factor affecting the mechanical characteristics of calcareous sand, but at present, most of relative studying methods rely on physical experiments. In order to study the influence of particle crushing characteristics on the micromechanics of calcareous sand, the 14-fragment replacement method satisfying the Apollonian distribution is used to simulate the calcareous sand particles, and the fragment replacement method (FRM) is used to simulate the particle crushing. The three-dimensional discrete element model of calcareous sand particle crushing is established, and the development of relative crushing rate and the evolution laws of coordination number, porosity, and sliding contact ratio in triaxial consolidated drained shear test are analyzed. The results show that the three-dimensional model considering particle breakage can well reflect the micromechanical properties of the internal structure of the sample. The micromechanical response with and without particle crushing is quite different, which can be well reflected by the numerical test under high confining pressure. In addition, the modified relative crushing rate proposed by Einav based on the research of Hardin can better describe the relative crushing rate of calcareous sand under wide gradation and can provide a reference for the study of particle crushing characteristics of laboratory test of calcareous sand under wide gradation.